INVESTIGASI VARIASI KECEPATAN POTONG OPTIMAL PADA PROSES PEMESINAN BAJA AISI 4140 - Sobron Yamin Lubis (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
Determination of optimum cutting speed in the lathe process should be considered in order to produce minimal machining costs and maximum production. Research The determination of optimum cutting speed was done to investigate the effect of cutting speed when cutting AISI 4140 steel against cost and production obtained. This study was conducted experimentally using lathe and theoretical calculations to determine machining costs and the amount of production produced. The lathe process is carried out using carbide cutting tools for cutting of AISI 4140 steel metal. In this machining the data obtained is the cutting time of the machining process tail loading process then the data is incorporated into the equation together with the cutting force, the cost of the cutting tools, the workpiece, the cost labourers. Then from the calculation results obtained by graph machining cost and production amount. Based on the graph, it is observed minimal machining cost and maximum production amount to know the optimum cutting point. The results obtained .The increase in cutting rate gives effect to the increase of production quantity, while for calculation of machining cost has decreased. Machining time has a significant effect on the change of production quantity and machining cost. The optimal cutting speed (Vcopt) is 269 m / min.